2002
DOI: 10.1111/1467-8624.00505
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Emotional, Cognitive, and Behavioral Predictors of Peer Acceptance

Abstract: Integrating principles of differential emotions theory and social information-processing theory, this study examined a model of emotional, cognitive, and behavioral predictors of peer acceptance in a sample of 201 early elementary school-age children (mean age = 7 years, 5 months). A path analytic model showed that social skills mediated the effect of emotion knowledge on both same- and opposite-sex social preference, but social skills and verbal ability were more strongly related to opposite-sex peer acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
142
1
24

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(176 citation statements)
references
References 60 publications
9
142
1
24
Order By: Relevance
“…The results support suggestions that youngest members of the cohort might have more difficulty being accepted by their peers [10], which is consistent with evidence indicating that they are much more likely to be bullied than other children [9]. Conceivably, difficulties in reading, communication and attainment that are experienced by younger students, especially in the earlier years in school, might have an adverse impact on their socialization within their peer group [22,23].…”
Section: Discussionsupporting
confidence: 85%
“…The results support suggestions that youngest members of the cohort might have more difficulty being accepted by their peers [10], which is consistent with evidence indicating that they are much more likely to be bullied than other children [9]. Conceivably, difficulties in reading, communication and attainment that are experienced by younger students, especially in the earlier years in school, might have an adverse impact on their socialization within their peer group [22,23].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, Martin and Fabes (2001) showed that the more time boys spent playing with other boys, the more positive emotions they expressed. This positive emotional development could be seen as another mechanism for reducing antisocial conduct, by fostering the expression of more prosocial behavior in boys in competitive social situations (Mostow, Izard, Fine, & Trentacosta, 2002). In relation to girls' groups, our results suggest that their choice of affective-organized activities, as well as their cooperative style of resource management with girl partners, may be linked to well-being in intimate relationships (Bouchard, Lussier, & Sabourin, 1999), and could be seen as a mechanism for reducing emotional problems.…”
Section: Discussionmentioning
confidence: 67%
“…Also, social and emotional skills have a significant impact on engagement in appropriate relationships in middle childhood (Denham et al, 2003), reduce aggressive reactivity (Pavarini, Loureiro, & Souza, 2011), predict peer acceptance (Mostow, Izard, Fine, & Trentacosta, 2002), social and behaviour outcomes (Fine, Izard, Mostow, Trentacosta, & Ackerman, 2003), and responsible behavior (Bear, Manning, & Izard, 2003). The efficacy of the school-based programmes that promote social and emotional competences is well established (Greenberg et al, 2003), at a cross-cultural level (Kimber, Sandell, & Bremberg, 2008;Moreira, Crusellas, Sá, Petracchi, & Matias, 2010).…”
Section: Desenvolvimento E Avaliação Das Características Psicométricamentioning
confidence: 99%